Cross-correlation relationship between intellectual property objects value and its price-forming factors - Pozdnyakov, Y.; Lapishko, M.; Skybinska, Z. (Lviv Politechnic Publishing House, 2019)
Valuation/appraising of intellectual property rights objects, such as brands and goodwill, using the Costs Approach, is based on different economic indicators of enterprises business activity. These indicators are used as a primary data for market value determination. These indexes are differently related to the cost of brands, and statistical relationship between these parameters researches, indisputably, presents both theoretical and practical interest. Because of the cross-correlation relationship closeness between assets market value and these primary data parameters directly depend estimation results accuracy and reliability. The work is verification of basic hypothesis, in obedience to that at the valuation/appraising procedure performing as primary data may be recommended to use those indicator parameters, which are characterized with the closest statistical relationship and, respectively, the highest crosscorrelation coefficient. We assume that these intangible assets are able to change value characteristics in both directions and change the annual depreciation sign during the separate periods of economic life, made it positive or negative. The purpose of the article is to define the quantitative estimations of cross-correlation coefficients, which determinates statistical relationship closeness between primary data economic parameters in Costs Approach. To analyze the question of selling, general and administrative (SG&A) expenses part choice, which must be attributed to the trademark value; to execute this index optimization. To perform the comparative analysis of cross-correlation relationship between the intellectual property objects value and most widely used price-forming factors. To execute the got results interpretation; to execute the analysis of economic measurements reliability improving possibilities, performed by independent expert appraising/valuation methods, by its accuracy increasing. It means researching and determination the most suitable primary data indexes for the market value and depreciation/obsolescence dynamic time changes indexes of intangible assets special kind, such as trademark and goodwill. The general methodological base of the article is scientific and special for the subject sphere of knowledge methods of scientific cognition. The choice of methodological approaches is conditioned by the specific of the economic measurements which are executed by independent expert appraising/valuation methods. The research is grounded on mathematical simulation and mathematical statistic quantitative methods. Research methodology also envisages generalization of previous publications results from scientifically-research sources and open information reports about the enterprises economic indicators. Base principles of independent expert appraising/valuation made the general methodological basis of the article, in particular - principles of Utility, Substitution and The Highest and of The Best Use. To the certain methods of research belongs the method of cross-correlation analysis and specialized methodologies of optimization with the use of results error minimization criterion. The time value of money theory implementation, in particular, is well-proved for the past periods cash-flows transforming to the modern valuation date, by compounding operation performing. It is set that the closest is statistical relationship between the appraised trademark value indexes and accumulated costs of advertising expenses, which are the part of selling, general and administrative (SG&A) expenses. At brand appraising/valuation procedure is not recommended to apply any accounting book-keeping amortization indexes, as they are not the reliable indicator of Depreciation/Obsolescence. It is educed that these types of the researched assets depreciation sign depends on their information support and development expenses cash flows, invested by owner. It is set that during the period of trademark existence a multiple change of depreciation sign on the separate time periods is possible. It depends on sufficient informative and advertisement support implementation. Certainly the list of these price-forming factors must be taken into account at market value and Depreciation/Obsolescence determination procedure. It is well-proven that this class intangible assets estimation value in general case of normal profitable enterprise activity must be determined with application of increasing market value model with negative Depreciation/Obsolescence.
Keywords: intellectual property rights object; brand name; trademark; goodwill; independent valuation/appraising; accounting; market value; intangible assets; sign-changed Depreciation/ Obsolescence; estimation error; estimation accuracy; methodical approaches; 303.094.5; 330.133.2; 330.133.7